Value of biomarkers for predicting immunoglobulin A vasculitis nephritis outcome in an adult prospective cohort. Issue 9 (3rd November 2017) - Berthelot, Laureline; Jamin, Agnès; Viglietti, Denis; Chemouny, Jonathan M; Ayari, Hamza; Pierre, Melissa; Housset, Pierre; Sauvaget, Virginia; Hurtado-Nedelec, Margarita; Vrtovsnik, François; Daugas, Eric; ,; et al.
Abstract: Background: Henoch–Schönlein purpura, more recently renamed immunoglobulin A vasculitis (IgAV), is a systemic vasculitis characterized by IgA deposits. The current markers used to assess IgAV inaccurately evaluate the risk of nephritis occurrence and its long-term outcomes. The current study assessed biomarkers of nephritis outcomes. Methods: This French multicentre prospective study enrolled 85 adult patients at the time of disease onset. Patients were assessed for clinical and biological parameters and re-examined after 1 year. Immunoglobulins, cytokines, IgA glycosylation, IgA complexes and neutrophil gelatinase-associated lipocalin (NGAL) concentrations were assessed in blood and urine. Results: We identified 60 patients with IgAV-related nephritis (IgAV-N) and 25 patients without nephritis (IgAV-woN). At the time of inclusion (Day 1), the serum levels of galactose-deficient IgA1 (Gd-IgA1) and urinary concentrations of IgA, IgG, IgM, NGAL, interleukin (IL)-1β, IL-6, IL-8, IL-10, IgA–IgG and IgA–sCD89 complexes were higher in the IgAV-N patients than in the IgAV-woN patients (P < 0.005 for all comparisons). After follow-up (1 year), 22 patients showed a poor outcome. Among the tested markers, urine IgA at disease onset adequately reclassified the risk of poor outcome over conventional clinical factors, including estimated glomerular filtration rate, proteinuria and age (continuous net reclassification improvement = 0.72, P = 0.001; integrated discrimination improvement = 0.13, P = 0.009) in IgAV patients. Conclusions: Taken together, these results showed that serum Gd-IgA1 and urinary IgA, IgG, IgM, NGAL, IL-1β, IL-6, IL-8, IL-10, IgA–IgG and IgA–sCD89 complexes were associated with nephritis in IgAV patients. Urinary IgA level may improve patient risk stratification for poor outcome.